1972
DOI: 10.1111/j.1365-2362.1972.tb00578.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Correlates of Perceived Exertion in Continuous and Intermittent Exercise with the Same Average Power Output

Abstract: Abstrad. Perceived exertion waa measured using a linear grading scale, in three healthy males performing paired patterns of continuous and intermittent exercise with the same average power output. Intermittent exercise with work periods of 10 sec. alternating with recovery periods of loadless pedalling for 30 sec. was associated with lower perceived exertion grndes than when work periods were 30 or 120 sec. Perceived exertion, oxygen intake, ventilation, heart rate, and blood lactate concentration were all sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
2
5

Year Published

1973
1973
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 16 publications
9
37
2
5
Order By: Relevance
“…In a previous study (Edwards, Melcher, Hesser, Wigertz & Ekelund, 1972) it was found that the higher rating of perceived exertion in intermittent exercise was closely correlated with the greater heart rate, ventilation, oxygen intake and blood lactate concentrations in this form of exercise compared with continuous exercise with the same average power output. The present study investigates further the relative costs, in terms of the cardiorespiratory adaptations to exercise and utilization of local energy stores in muscle, of the two types of exercise.…”
Section: Introductionmentioning
confidence: 88%
“…In a previous study (Edwards, Melcher, Hesser, Wigertz & Ekelund, 1972) it was found that the higher rating of perceived exertion in intermittent exercise was closely correlated with the greater heart rate, ventilation, oxygen intake and blood lactate concentrations in this form of exercise compared with continuous exercise with the same average power output. The present study investigates further the relative costs, in terms of the cardiorespiratory adaptations to exercise and utilization of local energy stores in muscle, of the two types of exercise.…”
Section: Introductionmentioning
confidence: 88%
“…Further* since many physiological measures (eg., oxygLn consumption, heart rate, minute ventilation) also Increase as a function of Increasin$ work Intensity, the fact that RPE Increases as a function of these physiological measures (Borg and Underholm, 1967;Borg and Noble, 1974;Edwards et al, 1972;Ekblom and Goldharg, 1971) Is also not surprising.…”
Section: Ve;21ý/vcmentioning
confidence: 99%
“…As modalidades de exercícios utilizados nos estudos foram ciclo ergômetro (38%) 21,23,25,[27][28][29] , esteira (19%) 22,24,26 , exercícios resistidos (13%) 24 , ciclismo indoor (19%) 30,31,32 , jogos no Nintendo Wii (6%) 33 e ciclo ergômetro adaptado para piscina (6%) 24 . Dentre os protocolos utilizados nos artigos, quatro estudos aplicaram protocolos de teste com carga incremental (25%), um estudo aplicou carga decremental (6%), quatro estudos aplicaram carga contínua (25%) e sete estudos aplicaram carga intervalada (44%).…”
Section: Resultsunclassified
“…A percepção subjetiva de esforço foi correlacionada com a frequência cardíaca (FC), potência, taxa ventilatória, consumo de oxigênio, eficiente metabólico bruto e concentração de lactato sanguíneo. A percepção subjetiva de esforço e a frequência cardíaca (FC) foram correlacionadas em dez artigos, sendo que um estudo apresentou correlação muito forte (r = 0,90  1,00) 23 , cinco estudos apresentaram correlação forte (r = 0,70  0,90) 21,22,25,27,28 , dois estudos apresentaram correlação moderada (r = 0,50  0,70) 26,29 , um estudo apresentou correlação fraca (r = 0,30  0,50) 33 e um estudo apresentou correlação muito fraca (r = 0,00  0,30) 32 . Além disso, um estudo apresentou coeficiente de regressão alto para teste de esteira (70%, R 2 =0,70) e relativamente fraca para exercício resistido (27%, R 2 =0,27) 24 .…”
Section: Resultsunclassified